Algaecidal detoxifying nanocomposite, and preparation method and application thereof
Patent Information
- Application Number
- CN202510836333.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-21
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-21
AI Technical Summary
[0005]然而,针对Mlrs这一类大分子酶,传统载体存在一系列关键难题:孔径与酶尺寸不匹配,部分载体孔道狭窄无法充分包裹/锚定大分子酶,导致酶活性退出和流失,或者因空间限制导致构象变化、活性下降;表界面不适配,比如碳材料或无机颗粒与高分子酶的亲和力有限,甚至出现电性排斥和活性中心屏蔽,导致负载量和生物活性双低;环境适应性差,部分有机或无机载体易受pH、离子干扰,甚至存在生物毒性,难以适应复杂水环境中的持续应用需求
(1)本发明通过调控MSN合成制程中的扩孔剂的比例及反应条件,成功制备了孔径可调控的介孔二氧化硅。这种MSN不仅能实现与酶分子的精准空间匹配,还具备高比表面积和良好的生物相容性,有利于后续酶的高效负载和保持活性。
Smart Images

Figure CN120683090B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of material preparation and water pollution control, specifically to an algae-killing and detoxifying nanocomposite material, its preparation method, and its application. Background Technology
[0002] With the increasing globalization of industry and the intensification of eutrophication, cyanobacterial blooms, such as those caused by Microcystis, occur frequently, especially in closed or semi-closed aquatic environments like lakes and reservoirs. These blooms periodically release harmful substances such as microcystins (MCs), posing a significant threat to ecosystem safety, drinking water safety, and even human health. Existing physical, chemical, and biological methods for controlling Microcystis and cyanobacterial toxins each have their advantages and disadvantages, but they generally suffer from low efficiency, difficulty in recycling, secondary pollution, or long treatment cycles. Among numerous control strategies, bio-enzymatic degradation is becoming a research hotspot in this field due to its high specificity and environmentally friendly advantages.
[0003] In recent years, studies have shown that microcystin-degrading enzymes such as MlrA, MlrB, and MlrC possess unique spatial structures and high molecular weight characteristics, enabling them to specifically break specific bonds in MCs molecules, thereby achieving efficient and targeted degradation of algal toxins. These enzymes exhibit significant algal toxin degradation activity, providing new insights for the control of algal pollution and algal toxins. However, these enzymes have also encountered a series of bottlenecks in their application. First, as free enzymes, MlrA, MlrB, and MlrC have fragile natural conformations, easily deactivated and inactivated by environmental changes such as temperature, pH, and ionic strength, resulting in insufficient stability and significantly reduced degradation activity and lifespan. Furthermore, free enzymes are difficult to achieve efficient spatial anchoring, and cannot be easily recovered and reused after the reaction, increasing actual operating costs. Especially under the demand for rapid response and treatment of actual water pollution, the insufficient immobilization and recyclability of free enzymes severely restrict their industrial-scale promotion.
[0004] Based on this, researchers are constantly exploring various enzyme immobilization technologies to overcome the aforementioned challenges. Enzyme immobilization not only improves the stability and environmental adaptability of enzyme catalytic performance but also facilitates recovery and reuse, enhancing the economy and controllability of the catalytic system. Currently, there are many types of immobilization supports. For example, CN104569099A discloses a rapid phenol detection electrode that immobilizes tyrosinase by modifying reduced graphene oxide with 1-aminopyrene, utilizing the high specific surface area and good conductivity of graphene to improve detection sensitivity; CN105154428A discloses a carboxylated three-dimensional ordered mesoporous carbon-lysozyme composite material that immobilizes lysozyme through covalent cross-linking, utilizing the unique structure of mesoporous carbon to enhance enzyme activity and mass transfer efficiency; CN100359324C discloses a biosensor enzyme functional membrane containing exfoliated manganese dioxide, utilizing the large specific surface area and conductivity of manganese dioxide to enhance enzyme immobilization and activity.
[0005] However, traditional carriers present a series of key challenges for macromolecular enzymes like MlrA, MlrB, and MlrC: pore size mismatch with enzyme size, with some carriers having narrow pores that cannot adequately encapsulate / anchor the macromolecular enzyme, leading to enzyme activity loss or conformational changes and decreased activity due to spatial limitations; incompatible interfaces, such as limited affinity between carbon materials or inorganic particles and macromolecular enzymes, even resulting in electrostatic repulsion and active site shielding, leading to low loading capacity and low biological activity; poor environmental adaptability, with some organic or inorganic carriers susceptible to pH and ion interference, and even exhibiting biotoxicity, making them unsuitable for continuous application in complex aquatic environments. Furthermore, existing patents on enzyme immobilization methods primarily focus on small molecule enzymes or specific reaction systems, failing to address the issue of efficient and stable immobilization of macromolecular peptides like MlrA, MlrB, and MlrC. Currently, no published patents or literature have been found that anchor MlrA or MlrC to special carriers while simultaneously achieving loading efficiency, activity protection, and environmental stability.
[0006] Therefore, there is an urgent need to develop a new method for immobilizing MlrA, MlrB, or MlrC enzymes, as well as a novel algicidal and detoxifying nanocomposite material, to overcome the limitations of traditional immobilization carriers and fully leverage the anchoring advantages to achieve efficient and green control of microcystin toxins and harmful algal blooms. Summary of the Invention
[0007] To achieve one of the above objectives, this invention provides a novel algaecide and detoxifying nanocomposite material, its preparation method, and its application. This invention achieves efficient loading by controlling the pore structure of mesoporous silica (MSN) to match the molecular size of MlrA, MlrB, or MlrC enzymes, significantly improving enzyme immobilization efficiency and activity retention. This results in the efficient degradation and inhibition of cyanobacteria and their toxins in water, achieving a highly efficient, green, and safe method for controlling algae infestations and killing algae. The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a novel algae-killing and detoxifying nanocomposite material, comprising the following raw materials: algae toxin-degrading enzymes and nanomaterials of immobilized enzymes, wherein the algae toxin-degrading enzymes include one or more of MlrA, MlrB and MlrC, and the nanomaterials of immobilized enzymes include MSN.
[0008] Preferably, MlrA, MlrB, and MlrC all belong to the metalloproteinases encoded by the mlr gene cluster, and have highly similar amino acid sequences and catalytic cores. This makes them similar in terms of substrate binding mode and catalytic activity, and they can play similar roles in applications such as bioprocessing and drug development.
[0009] Preferably, the preparation method of the nanomaterial MSN includes the following steps: S1. At room temperature, the template agent, alkaline catalyst, and pore-expanding agent are mixed evenly, stirred and heated, and then the silicon source is added and stirred to obtain the MSN core; S2. Add an etchant to the above mixture and etch under heating conditions to obtain the nanomaterial MSN.
[0010] Preferably, the mass ratio of algal toxin-degrading enzyme to immobilized enzyme nanomaterial in the raw material is 1:(0.25-4).
[0011] More preferably, the mass ratio of the template agent, alkaline catalyst, pore expander, and silicon source is 1:(0.08-1):(3-6):(1-4); the template agent includes one or more of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecyl sulfate, and polyvinylpyrrolidone; the alkaline catalyst includes one or more of triethanolamine, ethylenediamine, tetraethylamine, or triethylamine; the pore expander includes one or more of triethanolamine, ethylenediamine, triethylamine, and trimethylbenzene; and the silicon source is one or more of tetraethoxysilane, triethoxysilane, sodium silicate, and dichlorosilane.
[0012] More preferably, the stirring time in step S1 is 10-60 min and the heating temperature is 50-100℃; the etching temperature in step S2 is 60-100℃ and the etching time is 1-5 h.
[0013] More preferably, the etching agent in step S2 includes any one or more of the following mixtures: ① a mixture of ethanol and hydrochloric acid in a volume ratio of 1:(5-20), ② a mixture of methanol and nitric acid in a volume ratio of 1:(5-20), ③ a mixture of ethanol and ammonia in a volume ratio of 1:(5-20), ④ a mixture of ethanol and sodium hydroxide in a volume ratio of 1:(5-20).
[0014] Secondly, the present invention provides a method for preparing a novel algaecide and detoxifying nanocomposite material, which, based on the above-mentioned method for preparing nanomaterial MSN, further includes the following steps: S3. Mix MlrA, MlrB or MlrC with MSN in a mixture of glycerol and water, stir at 30-100 rpm for 10-60 min at room temperature, centrifuge, and resuspend the precipitate in buffer to obtain CMlrs@MSN.
[0015] More preferably, the ratio of glycerol to water in step S3 is 1:(1-3).
[0016] More preferably, the buffer solution in step S3 includes one or more of phosphate buffer, Tris buffer, carbonate buffer, and borate buffer, and the pH range of the buffer solution is 6.5-8.0.
[0017] Thirdly, the present invention also provides the application of the novel algaecide and detoxifying nanocomposite material described in the first aspect above in the field of degrading algal toxins or inhibiting cyanobacterial growth.
[0018] Preferably, the algal toxin is selected from at least one of MC-LR, MC-YR, MC-RR and Nodularin, and the cyanobacteria is selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc, Anabaena and Fibrocystis.
[0019] Compared with the prior art, the advantages of the present invention are as follows: (1) This invention successfully prepared mesoporous silica with tunable pore size by controlling the proportion of pore-expanding agent and reaction conditions in the MSN synthesis process. This MSN can not only achieve precise spatial matching with enzyme molecules, but also has a high specific surface area and good biocompatibility, which is beneficial to the efficient loading and maintenance of enzyme activity in the subsequent process.
[0020] (2) This invention achieves efficient immobilization of MlrA and / or MlrB and / or MlrC on the MSN carrier. After immobilization, the enzyme molecules are stably anchored in the carrier, significantly improving the enzyme's catalytic activity, reusability, and environmental stability, and avoiding the problems of easy inactivation and difficulty in cycling of free enzymes.
[0021] (3) The Mlrs@MSN nanocomposite material of the present invention has good catalytic activity, is recyclable and has high environmental stability. It can continuously and efficiently remove algal toxins and inhibit the reproduction of cyanobacteria. It has wide application value for the ecological restoration and water purification of eutrophic water bodies such as drinking water sources, lakes and ponds.
[0022] (4) The Mlrs@MSN composite material of the present invention combines the excellent mass transfer performance of tunable pore size MSN with the efficient biocatalytic properties of immobilized enzymes, realizing "simultaneous degradation and continuous inhibition" of cyanobacteria and their toxins. In particular, the present invention is the first to discover that MlrA and / or MlrC can not only degrade algal toxins, but also directly inhibit or even kill cyanobacteria through enzymatic action, providing a new and efficient technical approach for the treatment of cyanobacterial pollution. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 The image shows scanning electron microscope (SEM) images of MSN and Mlrs@MSN in Embodiment 1 of the present invention. Detailed Implementation
[0025] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0026] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0027] In this document, the terms “containing,” “comprising,” or “including” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.
[0028] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0029] Mesoporous silica (MSN) is considered a new generation of highly efficient enzyme immobilization carriers due to its unique advantages. Mesoporous silica materials possess the following characteristics: tunable pore size—pore sizes can be controlled from 2-50 nm through synthesis processes, precisely matching the size of large-molecule enzymes to maximize loading capacity and spatial stability; high specific surface area and ordered pore structure—providing ample binding sites and excellent substrate / product exchange efficiency; easily functionalized surface—efficiency enzyme anchoring and microenvironment protection can be achieved through surface modification with hydroxyl, amino, and other functional groups; good biocompatibility and environmental safety—no risk of secondary pollution, suitable for a wide range of applications; and excellent chemical and thermodynamic stability, enabling long-term stable operation in complex aquatic environments.
[0030] This invention precisely matches the pore size of MlrA and / or MlrB and / or MlrC molecules at the nanoscale by controlling the proportion of pore-expanding agents and reaction conditions during MSN synthesis. This creates suitable space for enzyme entry and intercalation, preventing enzyme inactivation due to unsuitable pore size. Because Mlrs carry a negative charge and the MSN surface carries a positive charge, Mlrs bind tightly to MSN through electrostatic adsorption. By interfering with the photosynthetic metabolic pathway of cyanobacteria and efficiently degrading the algal toxins they release, Mlrs achieve the effect of inhibiting and killing cyanobacteria.
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0032] It should be noted that, in the embodiments of the present invention, the algal toxin degrading enzyme MlrA used was prepared according to the preparation example 1 of the specification of patent CN110407329B, and the algal toxin degrading enzymes MlrB and MlrC used were prepared according to the preparation method of MlrA.
[0033] Example 1 This embodiment screens and optimizes the conditions for preparing a novel algaecide and detoxifying nanocomposite material, and prepares the nanomaterial MSN with adjustable pore size and its immobilized algal toxin-degrading enzyme (MlrA@MSN), including the following steps: (1) Take 1g of cetyltrimethylammonium chloride (purchased from Shanghai Aladdin Co., Ltd.), 80mg of triethanolamine (purchased from Shanghai Aladdin Co., Ltd.), and 3g of tricresylbenzene (purchased from Shanghai Aladdin Co., Ltd.), mix them evenly at room temperature, stir at 80℃ for 30min, then add 2g of tetraethoxysilane (purchased from Shanghai Aladdin Co., Ltd.), stir at 80℃ for 20min to obtain the MSN core; (2) The MSN core was etched by adding 4 ml of anhydrous ethanol (analytical grade) and 40 ml of concentrated hydrochloric acid (analytical grade) to the above mixture, refluxed at 95°C for 3 h, then centrifuged at 9000 rpm for 5 min, and washed with pure water to obtain the nanomaterial MSN. (3) Take five samples of 0.05mg, 0.1mg, 0.2mg, 0.4mg and 0.8mg MlrA respectively, and stir them with 0.2mg MSN in 1ml glycerol and water mixture (500μL glycerol + 500μL water). Incubate at 80rpm for 30min, centrifuge at 9000rpm for 5min, and resuspend the precipitate in Tris buffer at pH=7 to obtain the nanocomposite material MlrA@MSN, which are recorded as samples 1, 2, 3, 4 and 5.
[0034] The protein content in the supernatant of MlrA@MSN incubated under the above different conditions was determined by high performance liquid chromatography to determine the immobilization rate of the immobilized enzyme. The immobilization amount of MlrA@MSN was calculated according to the following formula (1), and the activity recovery rate was calculated according to formula (2). The results are shown in Table 1.
[0035]
[0036] In the formula, c, v, and U represent the concentration, volume, and specific activity of MlrA in the supernatant after centrifugation, respectively. c0, v0, and U0 represent the concentration, volume, and specific activity of the MlrA sample, respectively. MSN and V MSN The initial concentration and volume of MSN added.
[0037] Table 1. Immobilization capacity and activity recovery rate of MlrA@MSN synthesized under different conditions
[0038] As shown in Table 1, with a constant MSN mass, increasing the mass of the enzyme MlrA increases the immobilization capacity. When MlrA reaches 0.4 mg / mL, the mass ratio of MlrA to MSN is 1:0.5, resulting in the maximum immobilization capacity of MlrA on MSN and the highest activity recovery rate. However, when MlrA exceeds 0.4 mg / mL, the unit immobilization rate of MlrA on MSN decreases, and the activity recovery rate no longer increases. Therefore, the synthesis conditions of sample 4 are suitable for the synthesis of MlrA@MSN.
[0039] Electron microscopy was performed on the MSN of the nanocomposite material in this embodiment and the MlrA@MSN of sample 4, as shown below. Figure 1 As shown, its microstructure is a spherical shape with uniform mesopores on the surface.
[0040] Example 2 This embodiment provides a method for preparing a novel algaecide and detoxifier nanocomposite material (MlrB@MSN), comprising the following steps: (1) Take 1g of hexadecyltrimethylammonium chloride (purchased from Shanghai Aladdin Co., Ltd.), 1g of triethanolamine (purchased from Shanghai Aladdin Co., Ltd.), and 3g of tricresylbenzene (purchased from Shanghai Aladdin Co., Ltd.), mix them evenly at room temperature, stir at 100℃ for 10min, then add 4g of tetraethoxysilane (purchased from Shanghai Aladdin Co., Ltd.), stir at 80℃ for 20min to obtain the MSN core; (2) The MSN core was etched by adding 4 ml of anhydrous ethanol (analytical grade) and 20 ml of concentrated hydrochloric acid (analytical grade) to the above mixture, refluxed at 100°C for 1 h, then centrifuged at 9000 rpm for 5 min, and washed with pure water to obtain the nanomaterial MSN. (3) Take 0.4 mg of MlrB sample and 0.2 mg of MSN in 1 ml of glycerol and water mixture (500 μL glycerol + 500 μL water), stir, incubate at 80 rpm for 30 min, centrifuge at 9000 rpm for 5 min, resuspend the precipitate in Tris buffer at pH=8 to obtain the nanocomposite material MlrB@MSN.
[0041] The MlrB@MSN loading in Example 2 was 462.39 mg / g, and the activity recovery rate was 47.62%, according to tests and calculations.
[0042] Example 3 This embodiment provides a method for preparing a novel algaecide and detoxifier nanocomposite material (MlrC@MSN), comprising the following steps: (1) Take 1g cetyltrimethylammonium chloride (purchased from Shanghai Aladdin Co., Ltd.), 500mg triethanolamine (purchased from Shanghai Aladdin Co., Ltd.), and 6g thylbenzene (purchased from Shanghai Aladdin Co., Ltd.), mix them evenly at room temperature, stir at 50℃ for 60min, then add 1g tetraethoxysilane, stir at 80℃ for 20min to obtain the MSN core; (2) The MSN core was etched by adding 2 ml of anhydrous ethanol (analytical grade) and 40 ml of concentrated hydrochloric acid (analytical grade) to the above mixture, refluxed at 60°C for 5 h, then centrifuged at 9000 rpm for 5 min, and washed with pure water to obtain the nanomaterial MSN. (3) Take 0.4 mg of MlrC sample and 0.2 mg of MSN in 1 ml of glycerol and water mixture (500 μL glycerol + 500 μL water), stir, incubate at 80 rpm for 30 min, centrifuge at 9000 rpm for 5 min, resuspend the precipitate in phosphate buffer at pH 6.5 to obtain the nanocomposite material MlrC@MSN.
[0043] The MlrC@MSN loading in Example 2 was 419.96 mg / g, and the activity recovery rate was 43.25%, according to tests and calculations.
[0044] Example 4 This embodiment verifies the excellent catalytic ability of MlrA@MSN.
[0045] Take MlrA@MSN prepared from Sample 4 of Example 1, add MC-LR to 50 mM phosphate buffer (PBS, pH=7.0) to a final concentration of 0.25 μg·mL⁻¹, then add MlrA@MSN to a final concentration of 12.5 mg·L⁻¹. Incubate the reaction mixture at 25°C for 5 min, then add phosphate to a final concentration of 0.2% (v / v) to terminate the reaction. After termination, centrifuge the mixture at 12000 rpm for 30 min at 4°C, and collect the supernatant for analysis. Quantitative analysis of residual MC-LR was performed using high-performance liquid chromatography (HPLC) equipped with a C18 column.
[0046] The chromatographic conditions were as follows: detection wavelength 238 nm, flow rate 1.0 mL·min⁻¹, injection volume 50 µL, column temperature 30°C, and detection limit 0.1 μg·L⁻¹. The mobile phase consisted of an aqueous phosphoric acid solution (solvent A, 0.05% v / v, pH=3.84) and acetonitrile (solvent B), with the following gradient program: initial equilibration with 10% B for 3 min; linear increase of B phase from 10% to 40% within 0–5 min; increase of B phase from 40% to 70% within 5–12 min; decrease of B phase from 70% to 10% within 12–12.5 min; and then maintenance at 10% B for 0.5 min. The results showed that, compared with free MlrA and MlrA@MSN, the degradation efficiency of intracellular and extracellular MC-LR was improved by 66.19% and 67.92%, respectively.
[0047] Example 5 This embodiment verifies the good thermal stability and acid and alkali resistance of MlrA@MSN.
[0048] The novel nanocomposite material MlrA@MSN and free bioenzyme MlrA were incubated for 1 h at different temperatures (25-70 °C) and different pH values (4.0-11.0). MC-LR was added to 50 mM phosphate-buffered saline (PBS, pH=7.0) to a final concentration of 0.25 μg·mL⁻¹, and then MlrA@MSN added at different concentrations was added to bring the final concentration to 12.5 mg·L⁻¹. The reaction mixture was incubated at 25 °C for 5 min, and then phosphate was added to a final concentration of 0.2% (v / v) to terminate the reaction. After termination, the mixture was centrifuged at 12000 rpm for 30 min at 4 °C, and the supernatant was collected for analysis. The residual MC-LR was quantitatively analyzed using high-performance liquid chromatography (HPLC) equipped with a C18 column to determine the remaining activity and assess its thermal stability and acid and alkali resistance.
[0049] Table 2 Thermal stability and acid / alkali resistance of MlrA@MSN and MlrA at different temperatures and pH values.
[0050] As shown in Table 2, the activity of MlrA@MSN is higher than that of MlrA within the temperature range of 25-70℃, indicating that MlrA@MSN has higher thermal stability. Furthermore, the optimal reaction temperature for MlrA@MSN is 40℃, at which point its activity is 1.59 times that of MlrA. The activity of MlrA@MSN is also higher than that of MlrA within the pH range of 3.0-11.0, indicating that MlrA@MSN has strong acid and alkali resistance.
[0051] Example 6 This embodiment verifies the algicidal effect of MlrA@MSN and free enzyme MlrA, using Microcystis aeruginosa, a common algae in cyanobacterial blooms, as an example. The specific steps are as follows: Microcystis aeruginosa FACHB-905 was cultured to the logarithmic growth phase. MlrA@MSN and MlrA were added to the Microcystis aeruginosa solution at the same enzyme concentration (OD680 of the algal solution was 0.2, and the algal cell count was 1×10⁻⁶). 8 In a study, BG11 was used as a blank control, MSN as a material control group, MlrA as a free enzyme control group, and MlrA@MSN as an experimental group. Samples were taken on days 0, 2, 4, and 6. After extraction with methanol, the chlorophyll a content was tested by colorimetry, and the inhibition rate was calculated.
[0052] As shown in Table 3, after 4 days of treatment, the cyanobacteria in the experimental groups with added MlrA@MSN and MlrA were significantly inhibited, with inhibition rates of 63.94% and 53.39%, respectively. After 6 days of treatment, the inhibition rates of cyanobacteria in the experimental groups with added MlrA@MSN and MlrA were 77.06% and 63.91%, respectively. MlrA@MSN showed a more efficient ability to inhibit the growth of Microcystis aeruginosa.
[0053] Table 3 Algal inhibition efficiency of MlrA@MSN and MlrA at different culture times.
[0054] Example 7 This embodiment verifies the detoxification effect of MlrA@MSN and free enzyme MlrA, using Microcystis aeruginosa, a common alga in cyanobacterial blooms, as an example. The specific steps are as follows: Microcystis aeruginosa FACHB-905 was cultured to the logarithmic growth phase, and MlrA@MSN was added to the Microcystis aeruginosa solution (OD680 of the algal solution was 0.2, and the number of algal cells was 1×10⁻⁶). 8 The concentrations of microcystins in the cyanobacteria were determined by the following criteria: BG11 (as blank control), MSN (as material control group), MlrA (as free enzyme control group), and MlrA@MSN (as experimental group). Samples were collected on day 6, and the levels of microcystins inside and outside cyanobacteria were measured using an ELISA kit to assess the microcystin degradation ability during the inhibition process. The results are shown in Table 4. In the BG11 blank control group, the microcystin concentration reached 672.19±8.21 μg / L, while in the MlrA@MSN treatment group, the microcystin concentration was only 227.73±3.2 μg / L, a decrease of 66.12%. The microcystin concentration in the MlrA treatment group was 370.61±5.4 μg / L. This indicates that MlrA@MSN can not only effectively inhibit algal growth but also more efficiently degrade the toxins released by algal cells.
[0055] Table 4. Intracellular, extracellular, and total algal toxin content after 6 days of BG11 treatment.
[0056] Comparative Example 1 This comparative study verifies the optimal effect of MSN as an immobilization carrier for algal toxin degrading enzymes. Commercially available SBA-15 and KIT-6 were selected as reference materials for multi-parameter comparison. The preparation method differs from that of sample 4 in Example 1 in that MSN was replaced with SBA-15 and KIT-6, while the rest are the same.
[0057] The comparison results are shown in Table 5. MSN's enzyme loading capacity reached 2.4 times that of KIT-6, while its specific activity was 1.6 times that of KIT-6. In terms of activity recovery, MSN was 2.2 times that of SBA-15, and its total activity was further increased to 2.6 times that of SBA-15. This phenomenon is attributed to the precise design of multi-scale interface engineering in this study. Based on the molecular characteristics of MlrA, the structural adaptability of MSN was optimized, thereby achieving a synergistic improvement in the performance of the immobilized enzyme.
[0058] Table 5 Comparison of MlrA immobilization efficiency on different carrier materials
[0059] In summary, this invention proposes a novel algicidal and detoxifying nanocomposite material and its preparation method, which can achieve the immobilization of MlrA, or / and MlrB, or / and MlrC, solving the defect of instability of free enzymes. At the same time, MlrA@MSN shows superior performance to free enzymes in inhibiting the growth of Microcystis aeruginosa and degrading algal toxins, thus expanding the application range of MlrA@MSN.
[0060] The embodiments described above are some, but not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A nanocomposite material for killing algae and detoxifying, characterized in that, The product comprises the following raw materials: algal toxin-degrading enzymes and nanomaterials of immobilized enzymes, wherein the algal toxin-degrading enzymes include one or more of MlrA, MlrB, and MlrC, and the nanomaterials of immobilized enzymes include MSN; the algal-killing and detoxifying nanocomposite material is obtained by compounding algal toxin-degrading enzymes and MSN in a mixture of glycerol and water; The mass ratio of algal toxin-degrading enzyme to immobilized enzyme nanomaterials in the raw material is 1:(0.25-4). The method for preparing the MSN includes the following steps: S1. Mix the template agent, alkaline catalyst, and pore-expanding agent evenly, stir and heat, then add the silicon source and stir to obtain the MSN core; S2. Add an etchant to the above mixture and etch under heating conditions to obtain the nanomaterial MSN; The mass ratio of the template agent, alkaline catalyst, pore expander and silicon source is 1:(0.08-1):(3-6):(1-4); The etching agent in step S2 includes any one or more of the following mixtures: ① a mixture of ethanol and hydrochloric acid in a volume ratio of 1:(5-20), ② a mixture of methanol and nitric acid in a volume ratio of 1:(5-20), ③ a mixture of ethanol and ammonia in a volume ratio of 1:(5-20), ④ a mixture of ethanol and sodium hydroxide in a volume ratio of 1:(5-20). The template agent is hexadecyltrimethylammonium bromide; the alkaline catalyst is triethanolamine; the pore-expanding agent is thiol; and the silicon source is tetraethoxysilane. The stirring time in step S1 is 10-60 min, and the heating temperature is 50-100℃; the etching temperature in step S2 is 60-100℃, and the etching time is 1-5 h.
2. A method for preparing the algaecide and detoxifying nanocomposite material as described in claim 1, characterized in that, Includes the following steps: A1. Place the algal toxin degrading enzyme and MSN in a mixture of glycerol and water, stir and centrifuge; A2. Resuspend the precipitate in buffer solution to obtain Mlrs@MSN.
3. The method according to claim 2, characterized in that, The buffer solution in step A2 includes one or more of phosphate buffer, Tris buffer, carbonate buffer, and borate buffer, and the pH range of the buffer solution is 6.5-8.
0.
4. The application of the algae-killing and detoxifying nanocomposite material as described in claim 1 in the field of degrading algal toxins or inhibiting cyanobacterial growth.
5. The application of the algae-killing and detoxifying nanocomposite material according to claim 4, characterized in that, The algal toxin is selected from at least one of MC-LR, MC-YR, MC-RR and Nodularin, and the cyanobacteria is selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc, Anabaena and Fibrocystidia.
Citation Information
Patent Citations
Enzyme function sensitive membrane containing stripped MnO2 for biosensor and preparation method thereof
CN100359324C
Rapid phenol detecting electrode and preparation method thereof
CN104569099A
Carboxylated three-dimensional ordered mesoporous carbon-lysozyme composite material as well as preparation method and application thereof
CN105154428A
Novel nano material and immobilized enzyme and application thereof
CN119661866A